2020
DOI: 10.12681/healthresj.25302
|View full text |Cite
|
Sign up to set email alerts
|

The attιtudes and behavιors of intensιve care unιt nurses towards end-of-lιfe care

Abstract: Introduction: The end-of-life period is a process in which anxiety of death is experienced intensely and there are positive and negative experiences for the nurse and the patient. Nurses' attitudes and behaviors about death affect the quality of care in the end-of-life process.Aim: The aim of the present study was to determine the attitudes and behaviors of intensive care unit nurses towards end-of-life care.Material and Method: The studied sample consisted from 216 nurses working in the intensive care units o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This finding matched with El-Sayad and Shaala (22) who conducted a study in Egypt about "Palliative Care Education: Its Effect on Nurses' Competency during Care of Dying Patients" and reported that about two thirds of nurses had associated degree. On the other hand, the previous findings were contrasted with Hançerlioğlu and Konakçı (23) who conducted a study in Karnataka, India about "The attitudes and behaviors of intensive care unit nurses towards end-of-life care" and revealed that the majority of the participants had bachelor degree in nursing.…”
Section: Discussionmentioning
confidence: 70%
“…This finding matched with El-Sayad and Shaala (22) who conducted a study in Egypt about "Palliative Care Education: Its Effect on Nurses' Competency during Care of Dying Patients" and reported that about two thirds of nurses had associated degree. On the other hand, the previous findings were contrasted with Hançerlioğlu and Konakçı (23) who conducted a study in Karnataka, India about "The attitudes and behaviors of intensive care unit nurses towards end-of-life care" and revealed that the majority of the participants had bachelor degree in nursing.…”
Section: Discussionmentioning
confidence: 70%